Urgensi Pendidikan Agama Islam Tehadap Pendidikan di Indonesia: Penelitian - Muhamad Fajri Faresi, Gilang; Permana, Diansyah; Rahman, Adun; Erika, Rista; Samsul Arifin, Bambang (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Education plays a strategic role in fostering national character and civilization. In Indonesia, the country with the largest Muslim population, Islamic Religious Education (PAI) occupies a crucial position within the national education system. Its importance extends beyond the spiritual aspect to the development of students' morals, ethics, and personalities. PAI serves as the foundation for developing a generation with noble character, responsibility, and social awareness. This study analyzes the importance of integrating Islamic values ​​into formal education, particularly in the face of the challenges of globalization, moral degradation, and the identity crisis of the younger generation. PAI serves as an ideological bulwark against the negative influences of external cultures and is an effective medium for instilling the values ​​of tolerance, peace, and diversity in accordance with the spirit of Bhinneka Tunggal Ika (Unity in Diversity). This study employed a literature review method with a qualitative-descriptive approach through document analysis, educational regulations, and research related to PAI in Indonesia. The results show that PAI plays a vital role in developing education that is not only cognitively oriented, but also affective and psychomotor. A comprehensive PAI curriculum has been shown to positively impact student behavior in schools and society.